Leaning Into The Wind : A Memoir Of Midwest Weather - Toth, Susan Allen (Book collections on Project MUSE., 2003)
Leaning into the Wind is a series of ten intimate essays in which Susan Allen Toth, who has spent most of her life in Iowa, Minnesota, and Wisconsin, reveals the ways in which weather has challenged and changed her perceptions about herself and the world around her. She describes her ever-growing awareness of and appreciation for how the weather marks the major milestones of her life.